Evaluation of the antimicrobial potential of Catharanthus roseusextract - Bhumika Arora; Shailendra Kumar
Catharanthus roseusL. (Apocyanaceae), also known as Madagascar periwinkle, is an evergreen herb with therapeutic qualities. The present study investigated the antibacterial activity of C. roseus leaf ethanol extract (Cr-LEE) against E. coli.The result indicated significant growth inhibitory activity of Cr-LEE on E. coli. The effects were dose-dependent. From our earlier research, GC/MS (Gas Chromatography-Mass Spectrometry) was also used to determine the significant phytoconstituents in the extract. The secondary metabolites present in the extract may individually or synergistically be responsible for the antibacterial action of C. roseus.